The Advantages of Connectivity Map Applied in Traditional Chinese Medicine - Jiang, Huimin; Hu, Cheng; Chen, Meijuan (Frontiers in Pharmacology, 2021)
Amid the establishment and optimization of Connectivity Map (CMAP), the functional relationships among drugs, genes and diseases are further explored. This biological application database has been widely used to identify drugs with common mechanisms, repurpose existing drugs, discover the molecular mechanisms of unknown drugs, and find potential drugs for some diseases. Complicated research of Traditional Chinese Medicine (TCM) has entered a new era in the wake of the development of bioinformatics and other subjects, such as network pharmacology, proteomics, metabolomics, herbgenomics and so on. TCM gradually conforms to modern scientific research, but there is still a torrent of limitations. In recent years, Connectivity Map has shown its distinct advantages in the study of the components of traditional Chinese medicine and the synergetic mechanism of traditional Chinese medicine formulas, hence the combination of them is inevitable.